Strength determination for rough substrate-coating interfaces with three-dimensional defect structure. (April 2023) - Klünsner, T.; Krobath, M.; Konetschnik, R.; Tritremmel, C.; Maier-Kiener, V.; Samardzic, D.; Ecker, W.; Czettl, C.; Mitterer, C.; Kiener, D.
Abstract: Quantitative information on the strength of interfaces between thin ceramic coatings and their substrates is crucial when aiming to understand their failure behavior. Many technically relevant substrate-coating interfaces are not ideally planar, but rather rough and contain stress concentrators forming three-dimensional defect structures. An example for such a realistic case, a polycrystalline diamond coating that partially penetrates voids and cavities in its Co binder-depleted WC-Co hard metal substrate, was investigated within the current work with respect to its unknown interface strength behavior. Special focus was laid on the influence of the applied load direction on the observed fracture behavior. Micromechanical specimens were produced via focused ion beam milling as geometry variants of a micro shear compression specimen with their loaded areas' relative inclination towards the substrate-coating interface varied from 0° to 88°. Specimen loading was performed until fracture with a flat punch indenter in a scanning electron microscope. The recorded fracture loads were associated with the spatial stress distributions at fracture via finite element-based analysis. A plateau of the determined maximum principal stress triggering fracture in the ceramic-ceramic interfaces was found for inclination angles ≥45°. This plateau value was identified as the interface strength by observation of the crack path at the substrate-coating interface via scanning electron microscopy and analysis of the effectively loaded interface area values. The presented novel material testing technique gives first and previously not accessible insight into the fracture behavior of rough substrate-coating interfaces with complex defect structure. Graphical abstract: Unlabelled Image Highlights: Substrate-coating interface strength determined for CVD diamond-coated hard metal by new materials testing technique. First-time strength determination for rough substrate-coating interfaces with three-dimensional defect structure. Specimen geometry variation facilitates previously not possible investigation of interface defect texture.